Determinants of Smallholder Oil Palm Farmers’ Participation in the KBMJ Cooperative, Bosar Maligas - Azhari, M Raihan; Intan, Dian Retno (Kadiri University - Faculty of Agriculture, 2026)
Indonesia is the world’s largest palm oil producer, where smallholder farmers play a strategic role in sustaining production and the global supply chain. The effectiveness of smallholder plantation management largely depends on the cooperative institutional performance, particularly in terms of the participation of cooperative members. This study aims to analyze the influence of service quality, motivation, and knowledge on cooperative members' participation in the Konsumen Bersatu Makmur Jaya Cooperative (KBMJ). The data were collected from 86 respondents selected through simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that service quality and knowledge have a positive and significant effect on cooperative members' participation, whereas motivation does not. These findings suggest that improving cooperative service performance and strengthening the knowledge of cooperative members regarding institutional benefits are more effective in enhancing their participation than relying solely on individual motivational factors.